Pedagogical scenario for Intergrated Teaching - Pham, Xuân Thanh (Journal of Technical Education Science, 2012)
Our Vocational Education and Training (VET) system has much changed recently to meet the current needs of personnel’s quality. And it is the change in teaching approach from tradition to competence based – the so called “intergrated teaching” is the latest that has been implemented and applied for a variety of VET colleges. In practice, however, many colleges have difficulties in applying this teaching method. It is because no clear basis has been given to explain why instructing design of pedagogical scenario has been vague and infeasible. The article discusses on the “integrated teaching” concept subject to experiential learning model and takes it as a base to design pedagogical scenario for integrated lectures.